2003
DOI: 10.1034/j.1600-6143.2003.30112.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Use of Mycophenolate Mofetil is Associated With a Reduction in the Incidence and Risk of Late Rejection

Abstract: To evaluate the association of long-term continuous (minimum 1 year) mycophenolate mofetil (MMF) vs. azathioprine (AZA) therapy with the incidence of late acute rejection, we analyzed 47 693 primary renal allograft recipients reported to the United States Renal Data System between 1988 and 1998. The primary study endpoint was acute rejection beyond 1 year after transplantation. Univariate Kaplan-Meier analysis and multivariate Cox proportional hazard models were used to investigate the risk of reaching the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 15 publications
3
57
0
1
Order By: Relevance
“…A similar effect has been seen in the 5-yr analysis of a recent clinical trial of cyclosporin A versus tacrolimus: the patients with more early rejection showed more late loss of GFR (16). Thus, one reason for the improved late stability of GFR is probably superior control of late rejection by the new immunosuppressive therapies (17). Late loss of CrCl after early rejection could reflect late recurrent or smoldering rejection after early rejection, possibly as a result of subclinical rejection (18,19).…”
Section: Discussionsupporting
confidence: 50%
“…A similar effect has been seen in the 5-yr analysis of a recent clinical trial of cyclosporin A versus tacrolimus: the patients with more early rejection showed more late loss of GFR (16). Thus, one reason for the improved late stability of GFR is probably superior control of late rejection by the new immunosuppressive therapies (17). Late loss of CrCl after early rejection could reflect late recurrent or smoldering rejection after early rejection, possibly as a result of subclinical rejection (18,19).…”
Section: Discussionsupporting
confidence: 50%
“…In this study, the decrease in the incidence of acute rejection partly account for this result, since rejection-free patients had also benefited from the MMF therapy [17]. Recently, the demonstration that MMF protects against the long-term deterioration of renal allograft function has suggested that this drug has a beneficial impact on chronic allograft nephropathy [18]. Two others studies support these results and show a significant reduction in late acute rejection risk [19] and long-term graft loss with MMF 1201.…”
Section: Discussionmentioning
confidence: 67%
“…On the other hand, maintenance therapy with MMF for a longer period could be required, as previously mentioned, to improve the long-term results [18,19,201. However, maintenance with MMF, with a 50% CsA reduction after the first year post-transplantation, could be an alternative cost-effective strategy [26].…”
Section: Discussionmentioning
confidence: 99%
“…In combination with a CNI, MMF is associated with a decreased relative risk of graft failure independent of its effects on acute rejection as opposed to AZA (17). MMF also provides significant protection against long-term deterioration of renal allograft function and prophylaxis against late rejection ]mt]1 yr after transplantation (16,18). Notably, leucopenia, anemia, and gastrointestinal side effects are common with MMF (19).…”
Section: Rationale Underlying Steroid and Cni Withdrawal/ Avoidance Rmentioning
confidence: 99%
“…MMF, an antiproliferative agent when used with CNI and corticosteroids, affords excellent protection from acute rejection with no accompanying intrinsic nephrotoxicity (15,16). In combination with a CNI, MMF is associated with a decreased relative risk of graft failure independent of its effects on acute rejection as opposed to AZA (17).…”
Section: Rationale Underlying Steroid and Cni Withdrawal/ Avoidance Rmentioning
confidence: 99%